Reconstruction of complex knee wounds with a distally based gracilis flap and gastrocnemius myocutaneous flap: A case report - Kwon, Hyeokjae; Lee, Seokui; Kim, Sunje; Song, Seung Han; Oh, Sang-Ha; Kim, Joo-hak; Kyung, Hyunwoo; Yang, Ho Jik; Ha, Yooseok (Frontiers in Surgery, 2023)
A gastrocnemius muscle flap is a versatile option for covering the proximal one-third of the lower leg and around the knee. On the other hand, it is of limited use in patients with short gastrocnemius muscle or insufficient volume. The authors present a case in which a knee soft tissue defect occurred in a very thin patient and was reconstructed using a gastrocnemius myocutaneous flap and a distally based gracilis flap as a supplementary flap.